Farm Level Transformation and Quality of Life: A Case Study of Barak Valley - Banu, Smrithi Waheeda (Journal of Global Economy, Business and Finance, 2026)
Agricultural performance can promote human development by ensuring food security for sustainable development, raising the per capita income, providing better amenities of life, improving the nutrition and health status of the people while raising the environmental sustainability through agricultural growth. On the other hand, human development expands the productivity of the farmers in the form of raising the skill of farming, giving access to modern technology, more market information, extension services etc. The present paper analyses the agro - human development linkage of Barak Valley. The methodology used in this study was by collection of primary data and field observations. Samples for statistics were taken from heads of rural households in selected Agricultural Development Circles of three districts of Cachar, Karimganj and Hailakandi in Barak Valley. The sample consisted of 450 Households. Each component of agricultural performance is analyzed with the help of factor indices. The factor indices assist to understand the actual scenario of agricultural situation of sample ADOs in Barak Valley. A number of indices have been constructed to address the objectives of the study which includes: (a) Agricultural Performance Index (API), (b) Human development by Quality of Life (c) Wealth Index, (d) Health Index, and (e) Education Index. All these indices have been constructed at the household level. Moreover, suitable statistical, regression techniques and econometric models have been used to analyze the relationship among concerned variables of the study.